2019
DOI: 10.1590/s1677-5538.ibju.2018.0682
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic parameters and Neutrophil / Lymphocyte ratio in the prediction of urethroplasty success

Abstract: Objective: The pathophysiology of urethral stricture and its recurrence remains vague and one of the important causes is progressive inflammation. It has been shown in recent years that the neutrophil / lymphocyte ratio is a marker of systemic inflammation and is associated with prognosis in many cardiovascular diseases, malignancies and chronic inflammatory diseases. We assessed simple systemic inflammation markers preoperatively and surgical techniques for urethral stricture recurrence after ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…Another study reported that the probability of spontaneous fistula closure increased as the NLR value decreased in patients who developed pancreatic fistula after distal pancreatectomy [13]. Topaktas et al investigated the effect of NLR in predicting the recurrence of urethral stenosis after urethroplasty and reported that NLR was ineffective in predicting the recurrence of urethral stenosis [14]. In the present study, no difference was found in the NLR values of patients who developed UCF.…”
Section: Discussioncontrasting
confidence: 42%
“…Another study reported that the probability of spontaneous fistula closure increased as the NLR value decreased in patients who developed pancreatic fistula after distal pancreatectomy [13]. Topaktas et al investigated the effect of NLR in predicting the recurrence of urethral stenosis after urethroplasty and reported that NLR was ineffective in predicting the recurrence of urethral stenosis [14]. In the present study, no difference was found in the NLR values of patients who developed UCF.…”
Section: Discussioncontrasting
confidence: 42%
“…The best of our knowledge, this study is the first study that evaluate the value or capacity of hematological parameters in predicting the complications of hypospadias repair in children. There are three studies that evaluated the impact of these parameters in recurrence of urethral stricture after surgical treatment in adults (10,11,22). Topaktas et al (22) had reported 117 adult cases with urethral stricture who underwent urethroplasty and assessed the correlation between the systemic inflammation markers and recurrence rate of urethral stricture after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There are three studies that evaluated the impact of these parameters in recurrence of urethral stricture after surgical treatment in adults (10,11,22). Topaktas et al (22) had reported 117 adult cases with urethral stricture who underwent urethroplasty and assessed the correlation between the systemic inflammation markers and recurrence rate of urethral stricture after surgery. They determined that neutrophil, lymphocyte counts, or their ratio are not the predictors for recurrence urethral stricture after urethroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…58 NLR was found not to predict stricture recurrence in patients undergoing urethroplasty. 61 Thus, while there has been significant interest in utilizing NLR and PLR to predict strictures in various clinical populations, the results have been mixed and more specific markers are needed to identify patients at risk.…”
Section: Urethral Strictures—fibroinflammatory Contributorsmentioning
confidence: 99%